2019
DOI: 10.1021/acs.energyfuels.8b04191
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydropyrolysis of Biomass Using Molybdenum Sulfide Based Catalyst. Effect of Promoters

Abstract: 11 Catalytic hydropyrolysis of beech wood was conducted in a fluid bed reactor at 450°C and a total pressure 12 of 26 bar. The differences in hydrodeoxygenation activity, selectivity and the resulting product composition 13 between sulfided Mo/MgAl 2 O 4 , CoMo/MgAl 2 O 4 or NiMo/MgAl 2 O 4 catalysts have been investigated. The 14 acidity and molybdate species in the oxide catalyst precursors were characterized with ammonia 15 temperature programmed desorption (NH 3-TPD) and Raman spectroscopy. The spent sulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 46 publications
1
55
2
Order By: Relevance
“…These two catalysts were chosen due to their well-known activity in HDO reactions [21][22][23][24][25][26][27][28][29][30], where the NiMo catalyst mainly promotes the removal of oxygen from phenols after it has saturated the aromatics (HDO pathway), while the CoMo to a larger extent promotes the direct removal of oxygen from phenol (DDO pathway) [27,[31][32][33][34]. At the applied temperatures in the fluid bed reactor the hydrogenation/deoxygenation of phenols are controlled by the thermodynamic equilibrium [20], thus it has been shown that the CoMo catalyst is the best choice for the fluid bed reactor [35]. In addition a catalyst with MgAl2O4 as support material was chosen for the fluid bed reactor because of its relatively high mechanical strength, which decreases the catalyst loss due to attrition.…”
Section: Catalystsmentioning
confidence: 99%
“…These two catalysts were chosen due to their well-known activity in HDO reactions [21][22][23][24][25][26][27][28][29][30], where the NiMo catalyst mainly promotes the removal of oxygen from phenols after it has saturated the aromatics (HDO pathway), while the CoMo to a larger extent promotes the direct removal of oxygen from phenol (DDO pathway) [27,[31][32][33][34]. At the applied temperatures in the fluid bed reactor the hydrogenation/deoxygenation of phenols are controlled by the thermodynamic equilibrium [20], thus it has been shown that the CoMo catalyst is the best choice for the fluid bed reactor [35]. In addition a catalyst with MgAl2O4 as support material was chosen for the fluid bed reactor because of its relatively high mechanical strength, which decreases the catalyst loss due to attrition.…”
Section: Catalystsmentioning
confidence: 99%
“…Catalytic hydropyrolysis is an efficient process for the direct production of diesel and gasoline type fuels from solid lignocellulosic biomass such as wood and agricultural residues [1][2][3][4][5]. Such fuels are necessary to reach the goal of becoming independent of fossil fuels, especially in the heavy duty and aviation sector, which are not immediately moving towards electrification.…”
Section: Introductionmentioning
confidence: 99%
“…More advanced techniques than one-step bio-oil upgrading are more promising. One option is to perform the HDO step in situ during fast pyrolysis as catalytic fast hydropyrolysis in a fluid bed reactor [4,16,[45][46][47][48][49]. In this way, reactive oxygenates can be upgraded immediately once they are formed, and more stable compounds such as phenols, can be deoxygenated downstream.…”
Section: Discussionmentioning
confidence: 99%